2004
DOI: 10.1021/jp047355f
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Photoluminescence Spectra of Si Species Encapsulated in Zeolite Supercages

Abstract: Photoluminescence (PL) spectra of Si species encapsulated in zeolite supercages are studied. It is reported that the chained Si species terminated partially with phenyl groups and with some unsaturated bonds are formed in zeolite supercages by the reaction with phenylsilane and they show PL around 4 eV (J. Phys. Chem. 2004, 108, 2501-2508). In the present paper they are reduced with hydrogen to prepare Si chained species terminated and saturated with hydrogen atoms. The PL spectra are deconvoluted to be four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Previous theoretical and experimental works support this hypothesis. Experimental and theoretical efforts have shown that the energy of the luminescence due to the Si nanoparticle increases as the size of the particle decreases once the quantum confinement regime has been reached (<5 nm). , Although the absolute value of the measured and calculated lifetimes vary considerably, the trend is that the lifetimes of Si nanosructures decrease as the energy of the luminescence increases (particle size decreases), ,,,, which is in agreement with the lifetime trends seen in Figure and Table .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Previous theoretical and experimental works support this hypothesis. Experimental and theoretical efforts have shown that the energy of the luminescence due to the Si nanoparticle increases as the size of the particle decreases once the quantum confinement regime has been reached (<5 nm). , Although the absolute value of the measured and calculated lifetimes vary considerably, the trend is that the lifetimes of Si nanosructures decrease as the energy of the luminescence increases (particle size decreases), ,,,, which is in agreement with the lifetime trends seen in Figure and Table .…”
Section: Resultssupporting
confidence: 79%
“…Previous time-resolved luminescence studies on silicon nanostructures, using conventional sources, have produced lifetimes that ranged from nanoseconds to milliseconds in magnitude, depending on size, morphology, method of preparation, energy, etc. Although there is considerable variation among the results, the general trend is that as the size of the particle decreasesthereby forming species with a higher energy, more direct bandgapthe lifetime of the emission decreases . In addition, there is the possibility of energy transfer from smaller particles to larger ones via a Forster-type mechanism, which would also tend to shorten the lifetimes of emissions from smaller particles.…”
Section: Resultsmentioning
confidence: 99%
“…With highly monodispersive SiQDs, more advanced self-assembled structures can be obtained, such as binary superlattices with gold nanoparticles [125]. Complex superstructures can also be achieved via a controlled growth in pre-defined superstructures, such as opals [126,127], zeolites [128,129], or periodic mesoporous silica [130,131]. Embedding SiQDs in chemically resistant polymer hybrids is yet another very interesting technique [132].…”
Section: Colloidal Siqdsmentioning
confidence: 99%
“…However, it is not easy to control the size distribution of small nanoparticles with a countable number of atoms (so-called clusters) using these methods. The matrix method, based on the incorporation of materials into the 3D regular system of voids and channels of zeolite crystals, could be an alternative technique for the fabrication of semiconductor nanoclusters with a controllable size distribution. , Many works have been reported on the nanoclusters incorporated into zeolite pores: semiconductors, metals, , and polymers. , The subnanometer and nanometer clusters are very interesting as they are intermediates between the molecules and the typical nanocrystals. Usually, the structure of nanoclusters is different from the structure of nanocrystals, which resembles the structure of bulk crystals .…”
Section: Introductionmentioning
confidence: 99%